Effect of supplemental ammonium chloride on biochemical changes and amelioration of experimental urolithiasis in goats - SENTHILKUMAR, R P; JAMES, C S; GANGADEVI, P; LALITHA KUNJAMMA, C R (The Indian Journal of Animal Sciences, 2014)
Effect of supplemental ammonium chloride on the biochemical changes and amelioration of induced urolithiasis was studied on 12 male Malabari goats of 9 to 12 months age, during the experiment of 84 days. Goats were divided into 2 groups (1 and 2) of 6 animals each and were fed individually at maintenance level. Calculogenic ration A contained 1.194% calcium, 0.0578% phosphorus and 1.202% magnesium. In addition, ammonium chloride was supplemented to the extent of 1% in ration B. Supplemental ammonium chloride did not have any significant influence on body weight gain, feed and protein efficiency and haematological parameters. Serum calcil.m and phosphorus concentrations were higher, whereas, concentration of serum magnesium was lower. Urine calcium and phosphorus levels significantly decreasedÂ  whereas urine magnesium and nitrogen levels remained unaffected. Apparent availability of calcium, phosphorus, magnesium and nitrogen were not influenced significantly. Supplemental ammonium chloride causes significant increase in per cent retention of calcium and phosphorus. Presence of visible sand like calculi and micro-calculi in the kidney with other gross histopathological lesions in the kidney and bladder as in group 1 were not observed in group 2, which confirmed the possible anticalculogenic effect of ration B. It is concluded that supplemental ammonium chloride was effective in the prevention of urolithiasis in goats when fed with high magnesium calculogenic ration possibly due to increased excretion of chloride ions in the urine.